An Intratumor Heterogeneity-Related Signature for Predicting Prognosis, Immune Landscape, and Chemotherapy Response in Colon Adenocarcinoma - Liu, Cong; Liu, Dingwei; Wang, Fangfei; Xie, Jun; Liu, Yang; Wang, Huan; Rong, Jianfang; Xie, Jinliang; Wang, Jinyun; Zeng, Rong; Zhou, Feng; Xie, Yong (Frontiers in Medicine, 2022)
Background: Colon adenocarcinoma (COAD) is a frequent malignancy of the digestive system with poor prognosis and high mortality worldwide. Intratumor heterogeneity (ITH) is associated with tumor progression, poor prognosis, immunosuppression, and therapy resistance. Methods: We obtained clinical information and gene expression data for COAD patients from TCGA database. The DEPTH2 algorithm was utilized to evaluate the ITH score. X-tile software was used to determine the optimal cutoff value of ITH score. The COAD patients were divided into high- and low-ITH groups based on the cutoff value. We performed univariate Cox regression and LASSO regression analyses to screen prognosis-related genes for the construction of ITH-related prognostic signature. The nomogram was used to predict the overall survival of COAD patients. The proportion and type of immune cells were evaluated by CIBERSORT and ESTIMATE algorithms. We assessed chemotherapy response and predicted small-molecule drugs for treatment. The expression of prognosis-related genes was validated by the UALCAN and Human Protein Atlas database. Results: The OS of the high-ITH group was worse than that of the low-ITH group. We constructed a five-gene signature consisting of CEACAM5, ENO2, GABBR1, MC1R, and SLC44A4. The COAD patients were divided into high- and low-risk groups according to the median risk score. The OS of the high-risk group was worse than that of the low-risk group. The nomogram was used to accurately predict the 1-, 3- and 5-year OS of the COAD patients. The stromal score, immune score, and ESTIMATE score of the high-risk group were significantly higher than those of the low-risk group, whereas tumor purity showed the opposite trend. The patients classified by the risk score had distinguishable sensitivity to chemotherapeutic drugs. Finally, two public databases confirmed that CEACAM5 and SLC44A4 were highly expressed in normal tissues compared with COAD tissues, and ENO2, GABBR1, and MC1R were highly expressed in COAD tissues compared with normal tissues. Conclusion: Overall, we identified an ITH-related prognostic signature for COAD that was closely related to the tumor microenvironment and chemotherapy response. This signature may help clinicians make more personalized and precise treatment decisions for COAD patients.